2018
DOI: 10.3758/s13421-018-0812-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognates interfere with language selection but enhance monitoring in connected speech

Abstract: The current study investigated the contribution of phonology to bilingual language control in connected speech. Speech production was elicited by asking Mandarin-English bilinguals to read aloud paragraphs either in Chinese or English, while six words were switched to the other language in each paragraph. The switch words were either cognates or noncognates, and switching difficulty was measured by production of cross-language intrusion errors on the switch words (e.g., mistakenly saying (qiao3-ke4-li4) instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 86 publications
4
25
0
Order By: Relevance
“…Both these findings reduce the likelihood that inattention during reading leads to intrusion errors in the read-aloud task. Previously, we suggested that reversed dominance and default language effects reflect global inhibition of the dominant language to allow language mixing (Gollan & Goldrick, 2018;Gollan, Schotter, et al, 2014;Ratiu & Azuma, 2017); the replication of this result in a different population of bilinguals implies broad applicability of this bilingual control mechanism (see also Li & Gollan, 2018). The persistent susceptibility of function words to intrusion errors is informative because in English, Spanish, and French, function words tend to be shorter than content words.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Both these findings reduce the likelihood that inattention during reading leads to intrusion errors in the read-aloud task. Previously, we suggested that reversed dominance and default language effects reflect global inhibition of the dominant language to allow language mixing (Gollan & Goldrick, 2018;Gollan, Schotter, et al, 2014;Ratiu & Azuma, 2017); the replication of this result in a different population of bilinguals implies broad applicability of this bilingual control mechanism (see also Li & Gollan, 2018). The persistent susceptibility of function words to intrusion errors is informative because in English, Spanish, and French, function words tend to be shorter than content words.…”
Section: Discussionmentioning
confidence: 66%
“…Reversed dominance effects. In previous studies (Gollan & Goldrick, 2016Gollan, Schotter, et al, 2014;Gollan et al, 2017;Li & Gollan, 2018;Ratiu & Azuma, 2017), bilinguals more often mistakenly replaced a word written in the dominant language with its nondominant languagetranslation equivalent than the opposite, an effect we refer to as reversed dominance. We replicated this pattern; Chinesedominant bilinguals were more likely to produce English intrusions, saying the English translation instead of the written Chinese word, than vice versa.…”
Section: Error Production Measuresmentioning
confidence: 87%
“…By manipulating the language context, the paradigms successfully simulated daily-life scenarios where language intrusion is more likely to occur. Compared to other tasks such as the reading aloud of texts (Gollan & Goldrick, 2018;Gollan et al, 2014;Li & Gollan, 2018;Schotter et al, 2019), the current paradigm is better suited to investigate failures to 'stay' rather than failures to switch. However, in the current study, bilingual participants were still asked to use both of their languages in quick succession, which makes the repeat trials still intrinsically different from the 'staying in the same language' situation in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that language intrusions have also been investigated extensively using a reading aloud task, where participants are asked to read aloud mixed-language paragraphs (Gollan & Goldrick, 2018;Gollan, Schotter, Gomez, Murillo & Rayner, 2014;Li & Gollan, 2018;Schotter, Li & Gollan, 2019). However, the fact that people can read aloud non-existing words suggests that reading aloud does not necessarily involve concept and lemma selection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation